Functional definition of NrtR, a remnant regulator of NAD+ homeostasis in the zoonotic pathogen Streptococcus suis. Issue 5 (13th February 2019) - Wang, Qingjing; Hassan, Bachar H.; Lou, Ningjie; Merritt, Justin; Feng, Youjun
ABSTRACT: NAD + is an enzyme cofactor required for the 3 domains of life. However, little is known about the NAD + biosynthesis and salvage pathways in the opportunistic pathogen Streptococcus suis . A genome‐wide search allows us to identify the NAD + salvage pathway encoded by an operon of nadR‐pnuC‐nrtR (from SSU05_1973 to SSU05_1971 on the reverse strand) in the S. suis 05ZYH33 that causes streptococcal toxin shock–like syndrome. The regulator of this pathway is Nudix–related transcriptional regulator (NrtR), a transcription regulator of the Nudix family comprising an N‐terminal Nudix‐like effector domain, and a C‐terminal DNA‐binding winged helix‐turn‐helix–like domain. Intriguingly, the S. suis NrtR naturally contains a single amino acid substitution (K92E) in the catalytic site of its Nudix domain that renders it catalytically inactive but does not influence its ability to bind DNA. Despite its lack of enzymatic activity, DNA‐binding activity of NrtR is antagonized by the effector ADP‐ribose. Furthermore, nrtR knockout in S. suis serotype 2 reduces its capacity to form biofilms and attenuates its virulence in a mouse infection model. Genome mining indicates that nrtR appears in a strain‐specific manner whose occupancy is correlated to bacterial infectivity. Unlike the paradigmatic member of NrtR family having 2 unrelated functions (Nudix hydrolase and DNA binding), S. suis 2 retains a single regulatory role in the modulation of NAD + salvage. This control of NAD + homeostasis contributes to S. suis virulence.—Wang, Q., Hassan, B. H., Lou, N., Merritt, J., Feng, Y. Functional definition of NrtR, a remnant regulator of NAD + homeostasis in the zoonotic pathogen Streptococcus suis . FASEB J. 33, 6055–6068 (2019). www.fasebj.org